2016
DOI: 10.1007/s00432-016-2130-7
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic study of benign and malignant pleural effusion

Abstract: This model is suitable to discriminate benign and malignant pleural effusion and CARD9 can be used as a new peptide biomarker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 54 publications
0
12
1
Order By: Relevance
“…Research on the role of CARD9 in malignant diseases, especially the role of CARD9-mediated immunity or inflammation in tumors has been a hotspot nowadays. Contrary to previous findings regarding the increase of CARD9 in tumors, our previous research found that CARD9 was decreased in malignant pleural effusion compared with benign pleural effusion, indicating an interesting role of CARD9 in lung cancer [9]. In this study, both TCGA database and our clinical cohort showed the mRNA and protein level of CARD9 were lower in NSCLC tissues than that in adjacent normal lung tissues.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Research on the role of CARD9 in malignant diseases, especially the role of CARD9-mediated immunity or inflammation in tumors has been a hotspot nowadays. Contrary to previous findings regarding the increase of CARD9 in tumors, our previous research found that CARD9 was decreased in malignant pleural effusion compared with benign pleural effusion, indicating an interesting role of CARD9 in lung cancer [9]. In this study, both TCGA database and our clinical cohort showed the mRNA and protein level of CARD9 were lower in NSCLC tissues than that in adjacent normal lung tissues.…”
Section: Discussioncontrasting
confidence: 99%
“…However, CARD9 appears to function differently in lung cancer. Our previous research on the difference of protein profiles of the benign and malignant pleural effusion by proteomics technology found that CARD9 was decreased in malignant pleural effusion, and the mechanism was not clear [9]. In the latest study of CARD9 in lung cancer, Qu et al [10] reported that CARD9 suppressed lung cancer development by inhibiting the expansion of myeloid-derived suppressor cells (MDSCs) and indoleamine 2,3-dioxygenase (IDO) production.…”
Section: Introductionmentioning
confidence: 99%
“…We previously summarized the clinical significance of CARD9 in a variety of tumor types (Table 1) including hepatocellular carcinoma, intestinal carcinoma, gastric carcinoma, kidney carcinoma, and malignant pleural effusion [16,17]. These studies suggest that high CARD9 expression is associated with tumor progression and poor survival rate [18][19][20][21][22]. However, preclinical studies in tumor-prone mouse models indicate that CARD9 plays a dual role in the carcinogenic process as it exhibits both a pro-tumor and/or anti-tumor activity [23][24][25][26].…”
Section: Card9 As a Central Integrator Of Immune Responsementioning
confidence: 99%
“…Pleural effusion is a commonly clinical manifestation and even appears as an initial symptom. It is still a clinical challenge to identify the malignant pleural effusion (MPE) or benign pleural effusion (BPE) due to a series of etiology agents ranging from tuberculosis to tumors . Because MPE could reduce the overall survival, it was vitally crucial to accurately distinguishing malignant from benign pleural effusion in order to manage MPE timely.…”
Section: Introductionmentioning
confidence: 99%
“…It is still a clinical challenge to identify the malignant pleural effusion (MPE) or benign pleural effusion (BPE) due to a series of etiology agents ranging from tuberculosis to tumors . Because MPE could reduce the overall survival, it was vitally crucial to accurately distinguishing malignant from benign pleural effusion in order to manage MPE timely. The gold diagnosis criteria for MPE including pleural biopsy and exfoliative cytologic pathology examinations could reach up to an average sensitivity 60%; however, these conventionally diagnostic methods were still inadequate or sometimes invasive .…”
Section: Introductionmentioning
confidence: 99%